The Power Complex: The WSU System's Response to Dissent in the Late 1960s - Pietsch, Anthony (My University, 2009)
In the late 1960s, liberal and radical students enrolled in the Wisconsin State University (WSU) System coalesced into organizations to challenge the policies of the System's administration. One of these liberal-left organizations was Students for a Democratic Society (SDS), a national student organization known for confronting educational and political establishments. In order to prevent SDS from creating dissent on their campuses, WSU administrators established new policies that prevented SDS from being recognized and then used these policies to create guidelines that gave the administration greater control over student life in general. Small numbers of African American WSU students also rebelled between 1968 and 1970, causing a systemwide crisis. After racially based vandalism and violence occurred on several WSU campuses, the administration bypassed traditional disciplinary practices and redefined due process within the System. As a result, the administration expanded its disciplinary authority, and ethnic minorities were left with minimal access to due process. By the end of the 1960s, the administration's reactions to these events had facilitated significant growth of power for the System's administrators.
Keywords: Students -- Political activity -- Wisconsin; Students for a Democratic Society; Student movements -- Wisconsin; Wisconsin. -- University-System; Wisconsin State University